Information Literacy Competence in Curtailing the COVID-19 Hoax in the People of Aceh - Hamdani M. Syam; Rizanna Rosemary; Nur Anisah (Ikatan Sarjana Komunikasi Indonesia, 2025)
Information literacy is defined as the ability to access publications, understand, and critically evaluate media content. The competence level of community in information literacy encompasses the regulation of message interpretation passing through online media. Therefore, this study aims to determine the information literacy competence of the Aceh people in curtailing COVID-19 hoax. The data collection technique used was a questionnaire, involving 1078 respondents who were in 5 study locations, namely Banda Aceh, West Aceh, Central Aceh, and North Aceh, and Langsa. The results showed that 836 (77.55%) respondents understood hoax as intentional fake news, while 576 (53.43%) indicated that it is inaccurate information. A total of 559 (51.86%) respondents were sometimes able to distinguish between hoax and true information. Furthermore, most respondents suggested that there is a need for socialization or education in the community to prevent the spread of hoax. By promoting information literacy, self-control over the publication received is carried out optimally, which is a solution to prevent cases of circulating hoax. Furthermore, information literacy is an effective method in dealing with false publications by introducing the characteristics of fake news, verification procedures, and following up on issues that are likely to fall into the hoax category. Keywords: Covid-19, Hoax, Information, Literacy